Safety and Efficacy of a tCD25 Preselective Combination Anti‐HIV Lentiviral Vector in Human Hematopoietic Stem and Progenitor Cells. (March 2015) - Barclay, Sharlie L.; Yang, Yimin; Zhang, Siruo; Fong, Ryan; Barraza, Alfonso; Nolta, Jan A.; Torbett, Bruce E.; Abedi, Mehrdad; Bauer, Gerhard; Anderson, Joseph S.
Abstract The successful suppression of human immunodeficiency virus (HIV) in the "Berlin Patient" has highlighted the ability of HIV‐resistant hematopoietic stem cells to offer a potential functional cure for HIV‐infected patients. HIV stem cell gene therapy can mimic this result by genetically modifying a patient's own cells with anti‐HIV genes. Previous attempts of HIV gene therapy have been hampered by a low percentage of transplanted HIV‐resistant cells which has led to minimal clinical efficacy. In our current study, we have evaluated the in vitro and in vivo safety and efficacy of a truncated/mutated form of human CD25 preselective anti‐HIV lentiviral vector in human hematopoietic stem cells. This preselective vector allows us to purify vector‐transduced cells prior to transplantation so an increased percentage of gene‐modified cells can be delivered. Here, we demonstrate the safety of this strategy with successful engraftment and multilineage hematopoiesis of transduced cells in a humanized NOD‐RAG1−/−IL‐2rγ−/− knockout mouse model. Efficacy was also demonstrated with significant protection from HIV‐1 infection including maintenance of human CD4+ cell levels and a decrease in HIV‐1 plasma viremia. Collectively, these results establish the utility of this HIV stem cell gene therapy strategy and bring it closer to providing a functional cure for HIV‐infected patients. Stem Cells2015;33:870–879